Penerapan Strategi Pembelajaran Bermain Peran Dalam Meningkatkan Motivasi Dan Prestasi Belajar Siswa Kelas XII IPS- SMA Negeri 8 Samarinda Tahun Pelajaran 2022/2023 - Munasih Munasih (Pusat Riset dan Inovasi Nasional, 2022)
Based on law No. 20 of 2003 chapter II article 3 concerning the national education system that education is education based on Pancasila and the 1945 Constitution of the Republic of Indonesia which is based on religious values, Indonesian national culture and responsiveness to demands for change era.